Pengaruh Financial Distress dan Ukuran Perusahaan terhadap Audit Delay pada Perusahaan Konstruksi yang Terdaftar di BEI - Yuantomi Rohmat Udin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Construction firms listed on the Indonesia Stock Exchange from 2022 to 2024 serve as the focus for investigating how financial distress and firm size impact audit delay, utilizing a quantitative framework anchored in multiple linear regression analysis. Secondary data sourced from the companies' financial statements underpin this examination, where financial distress receives measurement via the Zmijewski model and firm size finds proxy through the natural logarithm of total assets. The timeliness of financial reporting directly tied to audit delay holds paramount importance, as delays compromise information quality available to stakeholders. Partial tests reveal no significant effects from either financial distress or firm size on audit delay, a pattern echoed in simultaneous assessments showing joint insignificance of these variables. Such outcomes point to external influences outside the modeled scope, notably operational complexity, auditor quality, and procedural technicalities in auditing, as primary drivers of delays. For practitioners, these insights underscore the necessity of bolstering internal operational efficiencies alongside enhanced auditor collaborations to expedite financial disclosures. Subsequent investigations ought to incorporate further pertinent variables, fostering deeper and more holistic insights into the phenomenon.